(3JObjb GdMSGHGJ (B(1) /s - (3GdhbGO , SGej eMeOs ((3YeGf (B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2010)
(3ebOeI aj Yde GdJObjb h GdbhGYO GdYGeI dJObjb GdMSGHGJ , GdGNWGA h GdZT , eObb GdMSGHGJ h COdI h bQGFf GdGKHGJ aj JObjb GdMSGHGJ , GdebheGJ GdGSGSjI degfI JObjb GdMSGHGJ h GdNWhGJ GdJfajPjI dgG , eaghe h CgOGa GdQbGHI GdOGNdjI h GdebheGJ GdGSGSjI dgG , Jbjje GdGOGA h YdGbJg HGdQbGHI GdOGNdjI , JObjb GdYedjGJ h GdJObjb Ydi YfGUQ GdeQcR GdeGdj , JbQjQ eObb MSGHGJ GdNGQLj h OhQ CLgRI GdOhdI aj GdQbGHI Ydi GdCehGd GdYehejI aj GdJQGK h GdJGQjN GdGSdGej (B.s
(3eQGLY U(B.265s
Keywords: (3GdMSGHGJs; (3eMGSHIs; (3eQGLYI GdMSGHGJs